NVX-CoV2373 induces humoral and cellular immune responses that are functionally comparable to vector and mRNA-based vaccines - Mai, Franz; Kordt, Marcel; Bergmann-Ewert, Wendy; Reisinger, Emil C.; Müller-Hilke, Brigitte (Frontiers in Immunology, 2024)
Background: After licensing of the protein-based vaccine NVX-CoV2373, three technically different vaccines against the SARS-CoV-2 became available for application to the human population - and for comparison of efficacies. Methods: We here recruited 42 study participants who had obtained one initial dose of NVX-CoV2373 and analyzed their immune responses in contrast to 37 study participants who had obtained either the vector vaccine AZD1222 or the mRNA vaccine BNT162b2 a year earlier. 32 participants also donated blood before first vaccination to serve as a vaccine-naive control. In detail, we investigated and quantified at day 21 and approximately six months after primary immunization the amounts of vaccine-specific antibodies produced, their neutralization capacity, their quality in terms of binding different epitopes and their efficiency in inducing various isotypes. Cellular immunity and intracellular cytokine production following in vitro re-stimulation with BNT162b2 vaccine was analyzed via ELISpot or via flow cytometry. Results: Our results show that even though vaccination including the mRNA vaccine yielded best results in almost any aspect of antibody levels and binding efficiency, the neutralization capacities against the wild-type Wuhan strain and the Omicron BA.1 variant early and at six months were comparable among all three vaccination groups. As for the T cells, we observed a prevailing CD8 response at three weeks which turned into a predominant CD4 memory at six months which has not yet been observed for AZD1222 and BNT162b2. While additional infection with SARS-CoV-2 resulted in a boost for the humoral response, T cell memory appeared rather unaffected. Conclusion: Whether any of these differences translate into real world protection from infection, mitigation of severe disease courses and prevention of long/post COVID will need to be investigated in the future.